ECONOMIC RECOVERY PROGRAM POST COVID-19 AT MODERN ISLAMIC BOARDING SCHOOLS (PESANTREN) - risanda (International Journal of Islamic Business and Economics (IJIBEC), 2022)
The things which need to be considered in pandemic is the economic sector recovery mechanism as a result of the Pembatasan Sosial Skala Besar policy, this research aims to build and develop a economic recovery program which is ideal for micro-businesses adopt especially pesantren in Semarang City, namely Smart Tren Program. This research uses an exploratory qualitative approach. Data sources obtained through observation, interviews and literature studies. The implementation of the Smart Tren Program is expected to: (1) increase the trust of existing customers and gain new potential customers; (2) renewal in the application of sophisticated technology in marketing; (3) expanding the market share of its superior products; (4) increasing the competitiveness of Islamic boarding schools in empowering the economy of the people. The success of this program will be determined by the seriousness of each stakeholder in carrying out this program in five stages, including: (1) data collection on the membership of Islamic boarding schools in Semarang City; (2) registering an account on the Smart Trends Program as a buye and a seller; (3) the product curration to ensuring that the products to be displayed in the Smart Trends Program have good quality and clear and complete product information; (4) Searching, ordering, paying, and shipping products from the required pesantren business unit.